Manipulation of processing technologies to enhance growth performance and (or) reduce production costs in pigs - Paulk, Chad Bennett (Kansas State University, 2011)
Nine experiments were completed to evaluate the effects of feed manufacturing practices on milling characteristics of diets and growth performance and stomach morphology in pigs. In Exp. 1 and 2, reducing the particle size of sorghum from 800 to 400 μm improved (P < 0.04) efficiency of gain in finishing pigs by 5% but had negative effects on cost of milling and stomach morphology. In Exp. 3 and 4, finishing pigs fed diets with 10 mg/kg of ractopamine HCl, had improved (P < 0.05) ADG, G:F, HCW, dressing percentage, and percentage carcass lean. However, increasing mix time of the diet from 0 to 360 s did not affect (P > 0.06) the response of finishing pigs to ractopamine HCl. In Exp. 5 and 6, adding ground and cracked corn to a pelleted supplement for nursery pigs decreased (P < 0.01) growth performance compared to feeding a complete pellet. In Exp. 7, increasing the percentage of cracked corn in a diet for finishing pigs decreased development of stomach lesions but also had a generally negative effect on efficiency of gain. In Exp. 8, adding cracked corn to a pelleted supplement (as done for the nursery pigs) decreased milling costs and improved health of stomach tissue. But, G:F was decreased by 6% (P < 0.05) which will make this technology unattractive to swine producers. In our final experiment (Exp. 9), pigs fed pellets tended to have the greatest growth performance, pigs fed mash the worst, and pigs fed pellets for only part of the grow-finish phase fell in between. In conclusion, grinding sorghum-based diets for finishing pigs improved efficiency of growth but extensive mixing to maximize diet uniformity had no effect on growth performance or carcass measurements. Use of cracked corn in diets does decrease diet costs and improve stomach health in finishing pigs but feeding of complete pellets for the entire finishing period supports maximum rate and (or) efficiency of gain.
Keywords: Pellet; Cracked corn; Particle size; Mix uniformity; Ulcers; Pigs; Animal Sciences (0475)